AI FOR GAMES - Millington, Ian. ([S.l.] : CRC PRESS, 2021)
What is artificial intelligence? How is artificial intelligence used in game development? Game development lives in its own technical world. It has its own idioms, skills, and challenges. That's one of the reasons games are so much fun to work on. Each game has its own rules, its own aesthetic, and its own trade-offs, and the hardware it will run on keeps changing. AI for Games is designed to help you understand one element of game development: artificial intelligence (AI).
OCLC-licensed vendor bibliographic record.
Keywords: Computer games -- Programming; Computer animation; Artificial intelligence; COMPUTERS / General; COMPUTERS / Artificial Intelligence; COMPUTERS / Computer Graphics / Game Programming & Design